The importance of accounting for business management (Research, Society and Development, 2025)
This article deals with the relevance of management accounting for business management, highlighting how this area of accounting can contribute to promoting financial sustainability, reducing bankruptcy rates and improving business efficiency. Poor management can have major consequences, such as the inability to achieve targets, reduced productivity, poor use of resources, loss of efficiency and competitiveness. This raises the question: How does management accounting contribute to financial sustainability and to reducing the rate of company closures in competitive markets? The general objective was to demonstrate the importance of management accounting as a strategic tool in promoting financial sustainability, increasing competitiveness and improving the efficiency of business management. The specific objectives were to identify the role of management accounting in promoting efficient management aligned with the objectives of sustainability and growth, to highlight its relevance to financial sustainability and to address its contribution to increasing the competitiveness of companies in the market. The methodology used was qualitative, exploratory and explanatory bibliographical research. The research shows that management accounting is an essential tool in supporting business management, providing managers with strategic and relevant information on the financial and operational reality of the organization, providing a more detailed view of the business, favoring accurate decision-making, directly contributing to the continuity and sustainable growth of the company, always with a focus on achieving its goals and objectives.